2003
DOI: 10.1038/sj.mp.4001191
|View full text |Cite
|
Sign up to set email alerts
|

D1 receptor alleles predict PET metabolic correlates of clinical response to clozapine

Abstract: A goal of pharmacogenetics is to clarify associations between allelic variation and risk factors in psychiatric illness. We report changes in regional brain metabolism based on dopamine alleles. Treatment-resistant schizophrenic subjects were positron emission tomography scanned with 18F-fluorodeoxyglucose after 5 weeks each of placebo and clozapine treatment. Significant regional brain metabolic effects were found for the D1 receptor genotypes (Po0.05), adjusted for multiple comparisons. Metabolic decreases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 27 publications
1
64
1
2
Order By: Relevance
“…An important area of future work would be to determine whether other atypical antipsychotic drugs that increase basal mPFC DA levels when administered systemically to animals (Meltzer et al, 2003) would also locally diminish mPFC DA release induced phasically by stress. Indeed, recent PET studies suggest that the highly efficacious drug clozapine may increase basal DA function in the PFC of schizophrenia patients (Cohen et al, 1997;Lahti et al, 2003;Molina et al, 2005a;Potkin et al, 2003). However, one exposure to amphetamine, which phasically increases cortical DA function in these patients, worsens their psychosis (Laruelle et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…An important area of future work would be to determine whether other atypical antipsychotic drugs that increase basal mPFC DA levels when administered systemically to animals (Meltzer et al, 2003) would also locally diminish mPFC DA release induced phasically by stress. Indeed, recent PET studies suggest that the highly efficacious drug clozapine may increase basal DA function in the PFC of schizophrenia patients (Cohen et al, 1997;Lahti et al, 2003;Molina et al, 2005a;Potkin et al, 2003). However, one exposure to amphetamine, which phasically increases cortical DA function in these patients, worsens their psychosis (Laruelle et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in the serotonin system may mediate clozapine response [64]. PET studies have shown that polymorphisms in the dopamine D1 receptor (DRD1) gene influence baseline metabolic activity in the dorsolateral frontal cortex in response to clozapine treatment [65,66]. These polymorphisms showed significant associations with changes in attention and working memory; two cognitive functions that are disrupted in Schizophrenia [56] and which are thought to, at least in part, be dependent upon prefrontal cortical function.…”
Section: Treatment Optimization: At the Interface Of Pharmacology Fumentioning
confidence: 99%
“…15 In terms of functional neuroimaging, diminished cortical metabolism, particularly in the pre-frontal region, was found to be associated with poor response to Clozapine in a SPECT study, 16,17 whilst in a recent PET study, patients who were poor responders to Clozapine (less than 30% of improvement in the BPRS) had diminished cortical metabolism, predominantly in frontal areas. 9 Recently, we have presented preliminar y data on neuropsychological aspects comparing patients with SRS to patients with TRS and it was found that SRS patients presented worse performance than patients with TRS. However, the sample size was too small to detect significant statistical differences.…”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, to date only one study has found a correlation between pharmacogenetic data with neuroimaging parameters. 9 Thus, there is a paucity of data regarding super-refractory schizophrenic patients which have still not been adequately studied, especially in terms of demographic and psychopathological aspects. Such an investigation is necessary to establish predictive factors of response to Clozapine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation